(پیکهاته ی کومه لگه له کوردستانی سه رده می ئه شکانیدا (کویله به نمونه - احمد, پ.ی.د. کۆزاد محمد; رضا, م.ی. هاژە عبد الجبار (Sulaimani Journal for Humanities, 2024)
It is obvious that slaves were regarded as an object or tool belonging to their owners in most ancient societies. Our sources of information about slaves and their conditions in Parthian society in the study area are very few and rare. Some of these sources, if any, rely on classical sources, written records and Sassanid documents. This study aims to focus on the most important and obvious sources that describe the condition of slaves, their types and even the sources of their origin, but also wants to raise the question of what the duties and rights (if given) were given to them. Whether the status of a slave would change and then he would become a free person or not. All sources constitute the evidence used to collect data for this study.
Keywords: ئەشکانییەکان دیلەکانی جەنگ دەستکەرت dastkart بەندەکbandak سۆفینی